Where the Money Goes - Pace, Nicholas M.; Zakaras, Laura (RAND Corporation, 2023)
This monograph provides a richly detailed account of the resources required by a diverse set of very large companies operating in different industries to comply with what they described as typical electronic-discovery requests and suggests ways to reduce those costs, as well as address concerns about duties to preserve data in anticipation of litigation.